1994
DOI: 10.1128/jvi.68.12.8254-8264.1994
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human immunodeficiency virus type 1 in human T cells by a potent Rev response element decoy consisting of the 13-nucleotide minimal Rev-binding domain

Abstract: Intracellular immunization is an anti-viral gene therapy strategy based on the introduction of DNA templates into cells to stably express genetic elements which inhibit viral gene expression and replication. We have recently developed an intracellular immunization strategy for human immunodeficiency virus (HIV) infection that uses RNA decoys. RNA decoys are short RNA oligonucleotides corresponding to the HIV trans activation response element (TAR) or Rev response element (RRE) sequences, which function by inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…1C) was constructed as previously described (9). The antisense-TAR sequences were derived from the HIV-1 MN isolate (20) and were expressed as a tRNA i Met -antisense-TAR fusion transcript in a double-copy vector design (1,27,28,50). The antisense-Tat/Rev gene used to generate the antisense-Tat/Rev retroviral vector GC-(anti-Tat/Rev)SN DC (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1C) was constructed as previously described (9). The antisense-TAR sequences were derived from the HIV-1 MN isolate (20) and were expressed as a tRNA i Met -antisense-TAR fusion transcript in a double-copy vector design (1,27,28,50). The antisense-Tat/Rev gene used to generate the antisense-Tat/Rev retroviral vector GC-(anti-Tat/Rev)SN DC (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, isolation of small peptides that bind avidly to target proteins has been difficult, probably because short peptides cannot adopt stably folded structures very readily (2). By contrast, short RNA molecules can form fairly stable structures through basepairing interaction (3), and RNA decoys have been reported that avidly bind and block a variety of proteins (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Expression of TAR and RRE decoy RNAs has been shown to render CD4 + T cells resistant to HIV replication by inhibiting the functions of the RNAbinding proteins tat and rev (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…By contrast, short RNA molecules can form fairly stable structures through basepairing interaction (3), and RNA decoys have been reported that avidly bind and block a variety of proteins (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Expression of TAR and RRE decoy RNAs has been shown to render CD4 + T cells resistant to HIV replication by inhibiting the functions of the RNAbinding proteins tat and rev (8)(9)(10)(11)(12). Furthermore, by using in vitro selection techniques, "designer" decoy RNAs have been isolated from large pools of random RNA molecules that bind with high affinity and specificity to several proteins, including a few that do not naturally interact with nucleic acids (13,(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Gene therapy approaches (intracellular immunization) were proposed in 1988 (3) as an alternative treatment modality for human immunodeficiency virus type 1 (HIV-1) infection. Several therapeutic genes, including transdominant mutant proteins (2,4,33,34), RNA decoys (13,32), ribozymes (21,37), and antisense sequences (7,11,28,30), have been evaluated preclinically (9). Multiple therapeutic genes (a transdominant Rev gene and RNA decoys) have been evaluated previously for their potential to inhibit HIV-1 replication in vitro (4,5,8).…”
mentioning
confidence: 99%